The conservation value of South East Asia's highly degraded forests: evidence from leaf-litter ants - Woodcock, Paul (The Royal Society, 2011)
South East Asia is widely regarded as a centre of threatened biodiversity owing to extensive logging and forest conversion to agriculture. In particular, forests degraded by repeated rounds of intensive logging are viewed as having little conservation value and are afforded meagre protection from conversion to oil palm. Here, we determine the biological value of such heavily degraded forests by comparing leaf-litter ant communities in unlogged (natural) and twice-logged forests in Sabah, Borneo. We accounted for impacts of logging on habitat heterogeneity by comparing species richness and composition at four nested spatial scales, and examining how species richness was partitioned across the landscape in each habitat. We found that twice-logged forest had fewer species occurrences, lower species richness at small spatial scales and altered species composition compared with natural forests. However, over 80 per cent of species found in unlogged forest were detected within twice-logged forest. Moreover, greater species turnover among sites in twice-logged forest resulted in identical species richness between habitats at the largest spatial scale. While two intensive logging cycles have negative impacts on ant communities, these degraded forests clearly provide important habitat for numerous species and preventing their conversion to oil palm and other crops should be a conservation priority.